Investigation of dielectric spectroscopy response in normal and cancerous biological tissues using S-parameter measurements. Issue 8 (24th May 2018) - Zubair, Kazi S.; Alhuwaidi, Sadiq A.; Song, Heather H.; Shellman, Yiqun G.; Robinson, William A.; Applegate, Allison J.; Amato, Carol M.
Abstract: Dielectric spectroscopy is conducted in terahertz frequency range to differentiate human normal tissues from the cancerous ones. Due to sensitivity of terahertz waves on water content of the biological tissues, when incident, it shows different dielectric constant values for normal and cancerous tissues. Analytical calculations using the Debye model, simulations using a 3D electromagnetic code, and measurements of the biological tissues employing free space technique were performed to investigate the difference in dielectric properties of the normal and cancerous tissues. New algorithm is developed to convert the measured transmission and reflection coefficients to dielectric constants. The biological samples were processed using various methods and measurement was performed for tissues from different parts of the body. The results show approximately 10% greater dielectric constant values for cancerous tissues, which is believed to be attributed to higher water content. The proposed terahertz dielectric spectroscopy may be used to identify the cancer tissues.